Control of pallets in automatic storage and retrieval system - Kafayat Oluwatoyin, Shobowale; Khan, Md. Raisuddin; Muhida, Riza (2009)
This research aims to develop a controller for pallet movement in the x and y direction for unit load AS/RS for parking lots. The controller and algorithm developed will be used for executing a puzzle like x and y motion to store and retrieve specific pallets. The mechanism consists of components such as Limit Switches, PIC, Gears, Geared DC motor, solenoid, shaft, rack and pinion. Array of Limit Switches are used for pallet identification. In the simulation, the rack and pinion mechanism is used to provide a substitute to the storage and retrieval machine used in AS/RS. The controller is made up of PIC16f777 and PIC16f877A connected together using serial peripheral interface (spi). PIC16f777 is used because of its ability to control motors and solenoids that are used to drive the shafts and in turn move the pallets. The controller and algorithm developed is capable of identifying and moving pallets in and out of the parking lot. This design can also be used for other products that can be stored in a warehouse.